Realigning Vocational Skills for Employment and Self Employment of Hearing- Impaired Youths: The Case of Masvingo-Peri Urban - Chenjerai Muwaniki; Patricia Muvirimi (Journal of Education and Vocational Research, 2018)
The study sought to investigate the prospects of equipping hearing impaired youths in peri-urban Masvingo District with skills for employment and self-employment in view of the economic crisis in Zimbabwe.  The study used the Human Capital Theory as the theoretical framework. A case study research design was used.  Data was collected through semi-structured interviews of eight purposefully selected hearing impaired vocational graduates as well as four key informant interviews with lecturers at the special school. Observations were also done to augment data from the interviews. Thematic analysis was used in analyzing the data. The study revealed that the hearing-impaired graduates acquired technical and vocational and skills at the special school. However, despite the high skill levels, they were not being utilized for their livelihoods. Instead of utilizing their technical and vocational skills, most of the graduates were engaged in self-initiated micro-entrepreneurial activities such as street vending. The major challenges to employment and self-employment included lack of capital, communication barriers and lack of representation and clear policy. The study recommends the realignment of vocational skills with the reality in which hearing-impaired graduates experience daily to focus more on entrepreneurship and community development in view of a weak economy which makes employment and self-employment difficult to achieve.